T-type and L-type calcium channel blockers for the treatment of cardiac iron overload: An update - Sirinart Kumfu (2018)
Copyright © 2017 Wolters Kluwer Health, Inc. All rights reserved. In patients with thalassemia, iron overload cardiomyopathy is a major cause of cardiac dysfunction and mortality. Despite many advances in the development of new iron chelating agents, heart failure still occurs in some patients and can lead to an increase in mortality rate. Recently, potential novel therapeutic strategies in the treatment of these patients have focused on L-type and T-type calcium channel blockers. These 2 channels have been reported as being the main routes for cardiac iron uptake under conditions of iron overload. In this review, the effects of these calcium channel blockers on both cardiac iron uptake and cardiac function under conditions of iron overload are discussed, and both consistent and inconsistent findings published in various studies are summarized and reviewed. Through this we hope to provide a greater insight into how future studies can most effectively use these drugs at the clinical trial stage.